A primary effect of palmitic acid on mouse oocytes is the disruption of the structure of the endoplasmic reticulum. Issue 1 (28th December 2021) - Wang, Yisu; Pope, Iestyn; Brennan-Craddock, Henry; Poole, Emma; Langbein, Wolfgang; Borri, Paola; Swann, Karl
Abstract : Exposure of mouse oocytes to saturated fatty acids (FAs) such as palmitic acid (PA) has been shown to increase lipid content and cause an endoplasmic reticulum (ER) stress response and changes in the mitochondrial redox state. PA can also disrupt Ca 2+ stores in other cell types. The links between these intracellular changes, or whether they are prevented by mono-unsaturated FAs such as oleic acid (OA), is unclear. Here, we have investigated the effects of FAs on mouse oocytes, that are maturated in vitro, using coherent anti-Stokes Raman scattering and two-photon fluorescence microscopy. When oocytes were matured in the presence of PA, there were changes in the aggregation pattern and size of lipid droplets that were mitigated by co-incubation in OA. Maturation in PA alone also caused a distinctive disruption of the ER structure. This effect was prevented by incubation of OA with PA. In contrast, maturation of mouse oocytes in medium containing PA was not associated with any significant change in the redox state of mitochondria or the Ca 2+ content of intracellular stores. These data suggest that a primary effect of saturated FAs such as PA on oocytes is to disrupt the structure of the ER and this is not due to an effect on the mitochondria or Ca 2+ stores.